Performance enhancement of fullerene based solar cells upon NIR laser irradiation1. Issue 60 (2nd July 2015) - Gill, Hardeep Singh; Thota, Sammaiah; Li, Lian; Kokil, Akshay; Mosurkal, Ravi; Kumar, Jayant
<x xml:space="preserve">Abstract</x> Photovoltaic performance enhancement of fullerene based solar cells was achieved upon exposure to near-infrared (NIR) laser pulses.